Aspect and Thematic Roles. (2nd February 2020) - Ogihara, Toshiyuki
Abstract: In this work, I propose a new semantic analysis of the Japanese progressive/resultative morpheme -te iru, which also leads to an improved account of the English progressive and contributes to cross-linguistic theory of aspect. The proposal is based on the modal analysis of the English progressive proposed by Portner (1998) and Ferreira (2016), but it is modified to accommodate the Japanese data. Crucially, the target state (resultative) reading of -te iru is available when the subject entity is a theme/undergoer; this is not controlled by the length of the event being described. To implement this idea, this work develops a formal system in which each thematic role predicate has its own temporal argument, and this time does not necessarily equal the temporal trace of the event in question. Specifically, a theme bears the target state role associated with an event e at a time that immediately follows the temporal trace of e . In addition, to describe and explain the behavior of -te iru, the traditional idea of "inertia worlds" according to which the relevant possible worlds are identical up to the utterance time is modified to allow them to differ in the past as well as in the future. It is noted that this modification is justified for the English progressive as well as for the Japanese -te iru form. This proposal allows us to predict that the behavior of achievements in English and Japanese is alike in simple past sentences and nominalized cases, but differs from each other in sentences containing the aspectual morphemes in question.